PTH-057 Influence of iron on gut microbial composition in acute dss-induced colitis in c57bl/6 mice. (17th June 2017) - Mahalhal, A; Campbell, B; Pritchard, DM; Probert, C
Abstract : Introduction: Iron deficiency anaemia is common in inflammatory bowel disease (IBD). Iron supplementation may induce or exacerbate colitis in rats ( APT 2001; 15:1989–99). Dysbiosis is common in IBD and iron contributes to this as it is a growth factor for some bacteria. We investigated the acute effect of dietary iron supplementation and/or reduction on the intestinal microbiome in a murine model of colitis. We report results of changes at the phylum level. Method: Studies were performed on six groups of wild-type mice (6/group). Acute colitis was induced with 2% dextran sodium sulphate (DSS) for 5 days, followed by 5 further days on water. DSS-treated mice were fed one of three diets (from day-1 of DSS treatment): Low iron [LI] (100ppm), normal iron [NI] (200ppm) and high iron [HI] supplemented (400ppm) chow. Also, three non-DSS-treated groups were studied and fed similarly. Clinical and pathological data were compared at day-1 vs. day-10, bacterial gDNA was extracted from faeces and microbiota composition determined from the sequence of V4 region of 16 S rDNA on the Illumina MiSeq platform. Statistical inferences were made using Welch's t-test with post-hoc analysis ( Bioinformatics 2010; 26:715–21). Results: DSS-induced colitis was exacerbated in LI and HI groups, more so in LI mice (as determined by mean total body weight loss [9.2%, at day-8] and significantly worse histology; median score 2.5, at day-10). However, faecal phyla changes were only seen following DSS treatment in the HI group at day-10 vs. day-1 with increased Proteobacteria (p<1.38e-3), Actinobacteria (p<5.13e-3) and Fusobacteria (p<3.25e-3), and decreased Firmicutes (p<6.96e-3) and Bacteroidetes (p<5.98e-3) as it illustrated in the figure below. Conclusion: DSS-induced colitis occurred in each group, but the severity was greatest in mice on low or high iron diets. Dysbiosis was only evident in mice receiving the high iron diet. These data suggest that 1) luminal iron may influence the severity of colitis, but 2) dysbiosis occurred when DSS was administered with the high iron diet, but not with low and normal iron diets. These findings suggest a role for iron in the dysbiosis seen during relapse of IBD and likely GI symptoms following iron supplementation. Disclosure of Interest: None Declared